A mosaic of independent innovations involving eyes shut are critical for the evolutionary transition from fused to open rhabdoms. - Mahato, S.; Nie, J.; Plachetzki, D.C.; Zelhof, A.C. (Developmental Biology, 2018)
A fundamental question in evolutionary biology is how developmental processes are modified to produce morphological innovations while abiding by functional constraints. Here we address this question by investigating the cellular mechanism responsible for the transition between fused and open rhabdoms in ommatidia of apposition compound eyes; a critical step required for the development of visual systems based on neural superposition. Utilizing Drosophila and Tribolium as representatives of fused and open rhabdom morphology in holometabolous insects respectively, we identified three changes required for this innovation to occur. First, the expression pattern of the extracellular matrix protein Eyes Shut (EYS) was co-opted and expanded from mechanosensory neurons to photoreceptor cells in taxa with open rhabdoms. Second, EYS homologs obtained a novel extension of the amino terminus leading to the internalization of a cleaved signal sequence. This amino terminus extension does not interfere with cleavage or function in mechanosensory neurons, but it does permit specific targeting of the EYS protein to the apical photoreceptor membrane. Finally, a specific interaction evolved between EYS and a subset of Prominin homologs that is required for the development of open, but not fused, rhabdoms. Together, our findings portray a case study wherein the evolution of a set of molecular novelties has precipitated the origin of an adaptive photoreceptor cell arrangement.